Transborder Ethnic Kin and the Dynamics of Peace Processes: Insights from the Kurdish Conflict. Issue 3 (3rd July 2019) - Arslan, Sinem
ABSTRACT: Previous literature explains peace negotiations mainly with country-level factors or events related to the countries where the peace efforts take place. This closed polity approach contrasts with contemporary peace processes where the actors and demands transcend nation-state boundaries. This paper challenges this dominant understanding in the peace process literature and focuses on the role of the rebel groups' transborder kin connections in affecting peace process dynamics. By studying the Kurdish Peace Process conducted between the Government of Turkey and the PKK, the paper argues that the transborder kin connections can both remedy and exacerbate bargaining problems acute to peace processes.